Overtopping reduction at Leixões Harbour, Portugal - Fernando Veloso Gomes (2005)
Overtopping of breakwaters is one of the main problems when dealing with harbours management. In the case of the Leixões Harbour, near Porto, Portugal, the inner area of the breakwater is used by an oil terminal, in which the security for operational reasons is an important aim. In order to study and improve the operational conditions of that oil terminal, reducing the overtopping events that fall upon the terminal or the access road during the year, a model of the breakwater section was built to be tested in a wave tank. The existent breakwater section was built in 1969 with a rubble mound tetrapods of 40 t, over an old submerged breakwater with cubic blocks of 90 t, built in 1940. The 1:60 scaled models were tested with different water depths, simulating different tidal levels, and different regular wave heights associated with different wave periods. Different breakwater profiles were tested, namely the original projected section (that was built), the actual profile (as built but with actual bathymetries) and new configurations (with submerged and berm breakwaters). The tests' images were recorded using a digital video camera and the water levels with hydrodynamic wave probes. In order to verify the behavior of the different profiles the overtopped volume of water was also recorded. The purpose of this paper is to present the results of these preliminary tests as well as the conclusions regarding the solution that reduces more the overtopping events, maintaining the mound stability and increasing so the operational conditions of the oil terminal. The results will show specially the effect of the submerged and berm breakwaters built with blocks of 90 t, in the reduction of overtopping events, when placed at a certain distance from the main structure.